MODELING OF BASIC PRINCIPLES OF ARTIFICIAL INTELLIGENCE IN SOLID MECHANICS PROBLEMS - Матченко, Т. І. (Proceedings of National Aviation University (archive), 2021)
The classification of the basic principles of development of artificial intelligence is carried out. The input parameters of the intelligent system for modeling materials jh with the specified properties are listed. The mechanism of modeling of expediency of development of artificial intelligence and the mechanism of synthesis of algorithm for the decision of an applied problem by artificial intelligence are offered. The form of the technical task for creation of a material with the set properties is developed.